Assessment of Etiological Factors Reported in the Literature and Their Impact on TMD Incidence in Young Adults - Wójcicka, Julia; Dudziński, Szymon; Charnushevich, Daniil; Musyt, Wiktoria (Quality in Sport, 2025)
Introduction: Chronic temporomandibular disorders (TMDs) typically result from long-term exposure to factors such as occlusal dysfunction, stress, and parafunctions, and are often associated with older patients. In contrast, young adults, exposed for a shorter time, may recover fully if diagnosed early. However, there is limited data comparing TMD treatment in young adults versus older individuals. Aim: To assess whether the development of TMD in young adults differs from that in the general population and whether a different treatment approach may be needed. Materials and Methods: Eighty-nine students aged 18–26 from various universities in Poznań completed a questionnaire and underwent clinical examination. Results: Muscular TMD diagnoses correlated with depression, stress, and surgical extraction of wisdom teeth. TMD presence was associated with anxiety, insomnia (AIS), pain (PS), and overbite. Parafunctional behaviors (OBC scale) correlated with anxiety, depression, stress, insomnia, and pain. Latent trigger points (TrPs) were significantly more frequent in TMD patients. Conclusions: Psychological factors significantly contribute to TMD in young adults, despite lower pain intensity compared to older patients. Occlusal factors and orthodontic treatment showed no correlation, while a link between wisdom tooth extraction and TMD was confirmed.